A glance at post-translational modifications of human thyroglobulin: potential impact on function and pathogenesis. Issue 3 (21st June 2022) - Tosatto, Laura; Coscia, Francesca
Abstract : Thyroid hormones are essential for the metabolism of vertebrates and their synthesis, storage and release in the thyroid gland are orchestrated by their large protein precursor thyroglobulin (Tg). Alterations of Tg structure and localisation often correlate with major thyroid disorders. Namely, Tg is the main antigen in autoimmune thyroid diseases, and mutations in its gene are one of the causes of congenital hypothyroidism. Post-translational modifications (PTMs) are crucial for Tg surface properties and may be affected by the disease microenvironment; yet, their role in thyroid homeostasis and pathogenesis remains elusive. The advance of electron cryo-microscopy (cryo-EM) has recently enabled the structure of Tg to be revealed in the un-iodinated and iodinated states. Moreover, ad hoc proteomic analyses have lately identified new PTMs in Tg. Here, we provide an overview of the Tg cryo-EM models obtained so far, and we build a three-dimensional map of known PTMs in Tg. Based on their location, we suggest the potential implication of each PTM in hormonogenesis, interactions with cellular partners, colloid cross-linking and hormone release. In addition, several PTMs overlap with immunogenic regions and pathogenic gene mutations. Hence, our analysis reveals a possible cross-talk between PTMs and alteration of Tg function in these disorders. In perspective, multi-omics analyses from patients, interpreted with structural and functional data, may generate more robust models to correlate phenotypes with classes of Tg functional alterations. This integrative approach will likely provide more targeted strategies to restore specific Tg functions in different thyroid pathologies.